Checklist to Meet Ethical and Legal Obligations to Critically Ill Patients at the End of Life - Robert W. Sibbald, Paula Chidwick, Mark Handelman and Andrew B. Cooper (Healthcare Quarterly, 2011)
Despite improvements in communication, errors in end-of-life care continue to be made. For example, healthcare professionals may take direction from the wrong substitute decision-maker, or from family members when the patient is capable; permit families to propose treatment plans; conflate values and beliefs with prior expressed wishes or fail to inquire about prior expressed wishes. Sometimes healthcare professionals know what prior expressed wishes are but do not respect them; others do not believe they have enough time to have an end-of-life discussion or lack the confidence, willingness and skills to manage one. As has been shown in initiatives to improve in surgical safety, the use of a checklist presents opportunities to potentially minimize common mistakes and errors. When engaging in end-of-life care, a checklist can help focus on what needs to be communicated rather than how it needs to be communicated. We propose a checklist to support healthcare professionals in meeting their ethical and legal obligations to patients at the end of life. The checklist should minimize common mistakes, and in situations where irreconcilable conflict is unavoidable, it will ensure that both healthcare teams and family members are informed and prepared.
Keywords: Robert W Sibbald, Paula Chidwick, Mark Handelman, Andrew B Cooper, end-of-life care, palliative care, healthcare ethics